The Effect of Oral Administration of Hypericum Perforatum on Serum Glucose and Lipids, Hepatic Enzymes and Lipid Peroxidation in Streptozotocin-Induced Diabetic Rats - Ghosian Moghadam, MohammadHassan; Ansari, Iman; Roghani, Mehrdad; Ghanem, Ali; Mehdizade, Neda (Galen Medical Journal, 2017)
Background: In this research, the beneficial effects of oral administration of Hypericum perfoÂratum (HP) on serum glucose and lipids, hepatic enzymes and the amount of malondialdehyde in Streptozotocin-induced diabetic rats are studied. Materials and Methods: In this experiÂmental study, 32 male rats where randomly divided into 4 groups of control, treatment-control, diabetic and treatment-diabetic. HP was orally administered to treatment groups over a period of 6 weeks. Serum glucose levels, triglyceride, total cholesterol along with HDL and LDL were all evaluated prior to initiation of the treatment, and at 3rd and 6th (last) week of treatment initiation, and in the end of the treatment, malondialdehyde and aminotransferase enzymes of the liver were evaluated. Results: regarding serum glucose levels and body weight measured in the 3rd and 6th week, the treatment-diabetic group didnâ€™t show a significant change compared to the diabetic group, regarding serum total cholesterol and LDL levels, a significant decrease was observed and regarding serum HDL, a significant increase was documented. Furthermore, treating the treatment-diabetic group with HP did not result in any significant decrease in serum triglyceride, malondialdehyde or alanine aminotransferase but, in fact, did cause a significant decrease in aspartate aminotransferase. Conclusions: Oral administration of HP did in fact have a beneficial effect on lowering serum levels of total cholesterol, LDL and the hepatic enzyme asÂpartate aminotransferase and on raising the levels of HDL in diabetized rats with Streptozotocin. [GMJ.2017;6(4):319-29] DOI: 10.22086/gmj.v6i4.889